Green Synthesis of Copper Nanoparticles (CuNPs) using Chaya (Cnidoscolus aconitifolius) Leaves Extract as a Bioreductant - Faricha, Yeni Askiyatul; Sutoyo, Suyatno (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Copper nanoparticles (CuNPs) are metallic particles sized 1-100 nm. This study was conducted to develop an ecofriendly and sustainable approach for CuNP synthesis using Cnidoscolus aconitifolius (chaya) leaves extract as a natural bioreductant. The research aimed to determine the optimal synthesis conditions, and characterize the resulting CuNPs. This experimental laboratory study employed a green synthesis method by reducing CuSO₄·5H₂O solution with chaya leaves extract. CuNPs were synthesized at various volume ratios (1:1, 1:2, 1:3, 1:4) and pH values (6-12). Data were collected using instrumental analyses (UV–Vis, FTIR, PSA, and XRD). The obtained data were analyzed descriptively based on spectral, structural, and particle size characteristics. The optimal synthesis condition was achieved at a 1:1 ratio and pH 10, producing CuNPs with a maximum absorption peak at 325 nm, an average particle size of 35.17 nm, and a polydispersity index of 0.2656. FTIR spectra indicated Cu vibrations, while XRD analysis shows the typical 2θ peaks for copper (32.57°, 35.60°, 38.72°, 48.91°, 53.32°, 61.67°, 68.02°, and 72.51°). These findings demonstrate the potential of chaya (Cnidoscolus aconitifolius) leaves extract as a sustainable bioreductant for green synthesis of copper nanoparticles, supporting the development of ecofriendly nanomaterials.